Acoustically Forced Droplet Combustion of Liquid Fuel with Reactive Aluminum Nanoparticulates. Issue 5 (3rd May 2020) - Sim, Hyung Sub; Plascencia, Miguel A.; Vargas, Andres; Karagozian, Ann R.
ABSTRACT: This experimental study explores the effects of acoustic excitation on burning droplets of liquid ethanol loaded with reactive aluminum nanoparticles (nAl). Continuously fed fuel droplet combustion and flame extinction (blowout) experiments were conducted in the vicinity of a pressure node (or velocity antinode) created in a closed acoustic waveguide, with a range of applied resonant forcing frequencies, pressure or velocity perturbation amplitudes, and particle loading concentrations. Simultaneous phase-locked OH* chemiluminescence and visible images were taken to quantify the influence of nanoparticle concentration on burning rate constant ( K ) and flame-acoustic coupling dynamics. In the presence of velocity perturbations, nAl-laden droplets were observed to burn for longer periods of time than they burned in the absence of acoustics, likely resulting from suppression of particle agglomerate formation and expulsion. It was found that at higher forcing frequencies, there were relatively greater enhancements in K values of nAl-loaded droplets than for lower frequencies. Interestingly, while at higher forcing amplitudes, the burning rate constant increased for a given loading concentration, that increase tended to be reduced at higher loading concentrations. Phase-locked imaging demonstrated that the presence of nAl increased the Rayleigh index ( G ) as compared with neat fuels under the same forcing conditions. Higher amplitude excitation leading to extinction showed that the addition of nAl could significantly increase the mean extinction strain rate, in some cases by up to 44%.